Satellite Observations Reveal a Large CO Emission Discrepancy From Industrial Point Sources Over China. Issue 5 (4th March 2022) - Tian, Yuan; Liu, Cheng; Sun, Youwen; Borsdorff, Tobias; Landgraf, Jochen; Lu, Xiao; Palm, Mathias; Notholt, Justus
Abstract: Irregular industrial Carbon monoxide (CO) emissions not only deteriorate global atmospheric environment but also add a large uncertainty to CO emission inventory. This work demonstrates the potentiality of the Tropospheric Monitoring Instrument (TROPOMI) data product to derive CO emissions from facility‐level industrial sources. We have demonstrated CO emission estimates of 14 randomly selected facility‐level industrial sources over China with uncertainties of 10%–35% from TROPOMI archive between 2017 and 2020. We found that most of the plumes reveal significantly larger emissions than the registered inventory values. The simplicity of the demonstrated plume quantification method makes it easily applicable everywhere around the globe. This study suggests that future CO satellite constellation can routinely observe point source CO emissions to support environment policy. Plain Language Summary: Irregular Carbon monoxide (CO) emissions from industrial sources add a large uncertainty to CO emission inventory. Some irregular CO emission events from industrial point sources in China may be not recorded properly by in situ monitoring system since enterprises may turn down the reporting values manually before discharging excessive pollutants to escape punishment. It is also expensive to carry out frequent airborne or ground‐based surveys across the entire industrial area to monitor such irregular CO emission events. This work demonstrates the potentiality of the Tropospheric Monitoring Instrument (TROPOMI) data product to derive CO emissions from facility‐level industrial sources. We have demonstrated CO emission estimates of 14 randomly selected facility‐level industrial sources over China with uncertainties of 10%–35% from TROPOMI archive between 2017 and 2020. We found that most of the plumes reveal significantly larger emissions than the registered inventory values. The simplicity of the demonstrated plume quantification method makes it easily applicable everywhere around the globe. This study suggests that future satellite constellation should monitor CO and co‐emitted gases with high spatial‐temporal resolutions and coverage, which can monitor routinely CO emissions to support environment policy. Key Points: Tropospheric Monitoring Instrument observations reveal a large Carbon monoxide (CO) emission discrepancy from industrial point sources over China Regional emission inventory probably underestimated CO emissions of certain industrial point sources over China Future CO satellite constellation together with monitoring local emissions could support environment policy